IDSA/ACEP/ASM/PIDS/SCCM/SHEA/SHM/SIDP Multisociety Position Paper: Hospital Strategies to Improve Sepsis Outcomes - Chanu Rhee; Henry Masur; Michael Klompas; Taison Bell; Lindsay M Busch; Kathleen Chiotos; David Classen; David Gilbert; Emily L Heil; Cindy Hou; Sameer S Kadri; Andre C Kalil; et al. (Clinical Infectious Diseases, 2026)
Abstract Sepsis remains a leading cause of morbidity and mortality in US hospitals despite extensive efforts to improve early recognition and treatment, particularly through implementation of the Centers for Medicare & Medicaid Services (CMS) SEP-1 quality measure. Recognizing the need for broader approaches to sepsis improvement, CMS and the Centers for Disease Control and Prevention are advancing new sepsis quality measures focused on outcomes and hospital programmatic capacity, while the Surviving Sepsis Campaign guidelines continue to provide evidence-based recommendations for bedside clinical management. However, there remains a need for practical, actionable guidance that complements existing guidelines and quality frameworks by addressing hospital-based strategies across the continuum of sepsis care. To address this gap, the Infectious Diseases Society of America convened a multidisciplinary, multisociety expert panel to develop a consensus-based position paper outlining evidence-informed recommendations for hospital-based sepsis improvement. The recommendations focus on infection-related aspects of sepsis management and span 6 domains: diagnostic testing and pathogen detection, antimicrobial management and delivery, surveillance and performance metrics, adjunctive therapy, program infrastructure and organizational support, and infection prevention. Examples include implementing multiplex nucleic acid amplification tests for positive blood cultures paired with active stewardship support; optimizing workflows for timely antibiotic delivery in septic shock; using clinical decision support to prioritize β-lactam administration before vancomycin when both are ordered; defaulting antipseudomonal β-lactams to prolonged infusion in critically ill patients; adopting EHR-based sepsis surveillance; tracking rates of inadequate empiric therapy, unnecessarily broad empiric therapy, antibiotic de-escalation, and timeliness of source control; establishing protocols for appropriate corticosteroid use in severe community-acquired pneumonia; and standardizing daily tooth brushing to prevent hospital-acquired pneumonia. The panel also highlights emerging approaches, particularly novel diagnostic strategies, that show promise but require further validation before widespread adoption. Collectively, these recommendations provide a pragmatic framework for hospitals to strengthen infection-related sepsis management and improve patient outcomes.